STEM-BASED INTERDISCIPLINARY PROJECTS: REPERCUSSIONS ON STUDENT ENGAGEMENT AND MOTIVATION (International Integralize Scientific, 2026)
STEM Education (Science, Technology, Engineering, and Mathematics) has gained recognition as a relevant pedagogical approach for developing 21st-century skills, especially when articulated with interdisciplinary projects that promote active learning. This article analyzes how interdisciplinary STEM-based projects contribute to student engagement and motivation in Basic Education, considering theoretical foundations, empirical evidence, and implementation challenges. The theoretical framework discusses the historical development of STEM, the relevance of interdisciplinarity, and the educational potential of project-based methodologies, connecting these elements to theories of motivation and student engagement. The analysis shows that integrated practices enhance meaning in learning, increase autonomy, and stimulate critical thinking, as described by Deci and Ryan (2000), Fredricks, Blumenfeld and Paris (2004), and Bybee (2013). Research also indicates that learning environments centered on real-world challenges strengthen students’ persistence, interest, and participation. However, limitations remain, such as insufficient teacher training and fragmented curricula. It is concluded that interdisciplinary projects grounded in STEM significantly foster engagement and motivation, provided they are supported by teacher professional development, collaborative planning, and adequate institutional conditions.
Keywords: STEM; interdisciplinarity; motivation; engagement; active learning